Volunteer Study of Contractile and Diastolic Function in the Horizontal and Head-Down Positions Using Transthoracic Echocardiography - Yoko Mukouyama; Mitsuharu Kodaka; Makiko Komori (Tokyo Women's Medical University Journal)
Background: The head-down position used in laparoscopic surgery considerably influences cardiac function. However, few studies have examined systolic and diastolic functions, such as the ejection fraction (EF), mitral annular plane systolic excursion (MAPSE), tricuspid annular plane systolic excursion (TAPSE), and early diastole/atrial kick ratio, in the head-down position. Methods: This study was registered at the University Hospital Medical Information Network (UMIN; Registration No.: 46067; Date: November 13, 2021). We used transthoracic echocardiography to examine the systolic and diastolic functions of the left and right ventricles after maintaining first horizontally and next head-down positions (30°) for 5 min in 31 adult volunteers. Results: Mean blood pressure increased by 6.4%, while left ventricular EF decreased from 70% to 63%. Similarly, MAPSE, which is strongly correlated with left ventricular EF, decreased by 11.3%. TAPSE, which correlated with right ventricular EF, increased by 8.7%. No change was observed in the early diastole/atrial kick ratio or E/E´, which reflects left ventricular diastolic function. Conclusions: In the head-down position, the EF, percentage fractional shortening, and MAPSE, which reflect contractility, decreased, whereas TAPSE increased. No significant differences were found in the measurement items reflecting diastolic capacity.